KAJIAN PROSEDUR AKUNTANSI KAS CV. TAUSAN - Ernawati Prehatin Lestari (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2022)
The purpose of this study was to examine the procedures for cash receipts and disbursements on CV. Tausan. This study uses qualitative data presentation techniques with descriptive analysis. In collecting the necessary data, the researcher used a triangulation technique, namely by conducting observations, interviews and documentation. The result is that the procedure for recording cash receipts and disbursements is not journalizing and posting the general ledger, which should be journalizing and posting the cash ledger.